Petrology, age, and tectonic setting of the Park Spur pluton, Aspy terrane, central Cape Breton Highlands, Nova Scotia, Canada - Smith, Amanda M.; Barr, Sandra M.; White, Chris E.; van Rooyen, Deanne; Sunatori, Évelyne (Atlantic Geoscience, 2023)
The Park Spur pluton was emplaced in the Aspy terrane of the central Cape Breton Highlands at 374.2 ± 2.9 Ma (U–Pb zircon). It consists mainly of muscovite-biotite monzogranite with small areas of garnet-bearing muscovite monzogranite and abundant pegmatite and aplite dykes. On its northern margin the pluton intruded metamorphic rocks of the Ordovician–Silurian Cape North Group and associated orthogneiss and on the south it intruded low-grade metamorphic rocks of the Silurian Calumruadh Brook Formation. Deformation along the southern margin of the Park Spur pluton is consistent with emplacement during dextral transpression between the Bras d’Or and Aspy terranes. The Late Devonian age combined with S-type petrological characteristics show that the Park Spur pluton and nearby Canal pluton are related to the ca. 375 Ma Black Brook Granitic Suite, all interpreted to have been emplaced during later stages of the Acadian orogeny in Ganderia as a result of delamination.